When is a career transition successful? a systematic literature review and outlook (1980–2022) - Mussagulova, Assel; Chng, Samuel; Goh, Zi An Galvyn; Tang, Cheryl J.; Jayasekara, Dinithi N. (Frontiers in Psychology, 2023)
A definition of career transitions was initially proposed by Louis in 1980. The pace of career transitions has since increased, unravelling traditional linear career pathways. Despite this, we have inadequate knowledge about what defines successful career transitions. Hence, we conducted a systematic review of the scholarship to understand how career transition success operationalized and to identify research gaps and directions. We identified and reviewed 244 articles on published from 1980 to 2022. We found that career transition success outcomes studied fall under the self-referent category, with the outcomes in the other-referent category absent. Further, most studies rely on a mix of objective and subjective success criteria, with no study considering possible interactions of the two. The review revealed a fragmented scholarship of career transition success and an urgent to broaden investigations of career transition success criteria in view of rapidly evolving employment trends globally.